1996
DOI: 10.1136/thx.51.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health-related quality of life in patients with chronic obstructive pulmonary disease.

Abstract: Background -The consequences of chronic obstructive pulmonary disease (COPD) on daily life, encapsulated by the term "health-related quality of life" (HRQL), are important in determining appropriate home care. There is a need to understand the relative contribution of respiratory impairment, physical disability, coping, age, and socioeconomic variables on HRQL. Methods -Patients with COPD were recruited on admission to a pulmonary rehabilitation centre. Respiratory impairment was assessed by lung function test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
111
3
19

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(147 citation statements)
references
References 27 publications
(1 reference statement)
13
111
3
19
Order By: Relevance
“…A relationship between the SGRQ total score and FEV 1, which is in agreement with several other studies, (5,(19)(20)(21)(22) was observed in this study. Our results did not show a relationship between body composition attributes and HRQoL.…”
Section: Discussionsupporting
confidence: 82%
“…A relationship between the SGRQ total score and FEV 1, which is in agreement with several other studies, (5,(19)(20)(21)(22) was observed in this study. Our results did not show a relationship between body composition attributes and HRQoL.…”
Section: Discussionsupporting
confidence: 82%
“…For example, Schrier, Dekker, Kaptein, and Dijkman (1990) found that elderly patients with CNSLD experienced substantial problems in the area of physical as well as psychological functioning and reported more dysfunction compared to a healthy control group. In accordance with other studies (e.g., Guyatt, Townsend, Berman, & Pugsley, 1987;Ketelaars et al, 1996;McSweeny, Grant, Heaton, Adams, & Timms, 1982;Williams & Bury, 1989), Okubadejo, Jones, and Wedzicha (1996) recently reported impairment in most areas of health status in patients with chronic obstructive pulmonary disease (COPD). However, gender differences have been given very little attention.…”
Section: Introductionsupporting
confidence: 78%
“…It is well established that in patients with COPD, the relationship between their physiological impairments and their health status measurements is generally weak (28,29). However, the correlation was generally lower with the French-Canadian questionnaires than reported in previous studies with the original English CRQ (7,30) and SGRQ (8,31). This rather poor correlation of the French-Canadian translated questionnaires and FEV 1 may be explained by the manner in which patients were selected and the type of intervention under study.…”
Section: Discussioncontrasting
confidence: 49%